Lessons from the Norwegian ATM System. - Hole, K.J.
This case study focuses on real-world ATM card misuse, illustrating how too much secrecy led to a deterioration of PIN-based authentication procedures, and why a bank's refusal to share technical information is a threat to customers during a conflict.
Keywords: Norwegian automatic teller machine system; PIN-based authentication; Automatic teller machine card misuse; Bank refusal; Technical information sharing